An Ethics of Recognition in Global and Teacher Education: Looking through Queer and Postcolonial Lenses. (1st January 2012) - Camicia, Steven
Global education and teacher education struggle to address a wide range of objectives surrounding curriculum. Some of these objectives are market-driven while others emphasise critical democracy. A theoretical framework is presented that combines literature from queer theory and postcolonial theory to better understand curriculum through a poststructural ethics of recognition. Recognising individuals and groups beyond normalising discourses and creating third spaces are the main themes of this ethics in curriculum work and global teacher education. These interpretations are illustrated with a brief example of a teacher education project that encouraged dialogue about global inequities and colonisation between pre-service teachers in the Philippines and the United States.